Optimizing Skin Quality via AI-Enhanced Physical Activity - Niki Tertipi; Eleni Sfyri; Vasiliki Sofia Grech; Vasiliki Kefala; Efstathios Rallis (Cosmetics, 2025)
Genetic predisposition, environmental factors, lifestyle choices, and physical activity influence skin quality. Regular exercise has well-documented benefits for skin physiology, including enhanced microcirculation, improved collagen synthesis, oxidative stress reduction, and modulation of inflammatory pathways. However, individual responses to physical activity vary significantly, depending on skin type, age, fitness level, and environmental exposures. Recent advances in artificial intelligence (AI) offer new opportunities for tailoring exercise programs to meet individual skin health needs. Wearable sensors and smart fitness devices provide real-time data on physiological responses (e.g., heart rate, sweat rate, and oxidative stress) and environmental parameters (e.g., UV exposure and pollution levels). AI algorithms process this data to create dynamic, adaptive exercise routines designed to maximize skin benefits while minimizing potential harm (e.g., exercise-induced oxidative stress in sensitive skin types). This review synthesizes the current evidence on the skin benefits of exercise while exploring the emerging role of AI-driven personalized physical activity as a novel tool in cosmetic dermatology. Integrating AI into fitness planning, personalized, non-invasive skincare strategies may complement traditional topical and procedural approaches, representing a step forward in precision dermatology.